Metabolic pathway of phenol degradation of a cold-adapted antarctic bacteria, Arthrobacter sp. - Lee, Gillian Li Yin; Zakaria, Nur Nadhirah; Futamata, Hiroyuki; Suzuki, Kenshi; Zulkharnain, Azham; Shaharuddin, Noor Azmi; Convey, Peter; Mohd Zahri, Khadijah Nabilah; Ahmad, Siti Aqlima (Multidisciplinary Digital Publishing Institute, 2022)
Phenol is an important pollutant widely discharged as a component of hydrocarbon fuels, but its degradation in cold regions is challenging due to the harsh environmental conditions. To date, there is little information available concerning the capability for phenol biodegradation by indigenous Antarctic bacteria. In this study, enzyme activities and genes encoding phenol degradative enzymes identified using whole genome sequencing (WGS) were investigated to determine the pathway(s) of phenol degradation of Arthrobacter sp. strains AQ5-05 and AQ5-06, originally isolated from Antarctica. Complete phenol degradative genes involved only in the ortho-cleavage were detected in both strains. This was validated using assays of the enzymes catechol 1,2-dioxygenase and catechol 2,3-dioxygenase, which indicated the activity of only catechol 1,2-dioxygenase in both strains, in agreement with the results from the WGS. Both strains were psychrotolerant with the optimum temperature for phenol degradation, being between 10 and 15 °C. This study suggests the potential use of cold-adapted bacteria in the bioremediation of phenol pollution in cold environments.